The relationship between emotional intelligence, anxiety, and performance in physical education and sport students - Zoghlami, Wael; Hawani, Aymen; Khiari, Hyem; Mnedla, Sofiene; Marsigliante, Santo; Elloumi, Ali; Muscella, Antonella (Frontiers in Psychology, 2023)
Emotional intelligence has been recently the main target in research on sports psychology. The objectives of this study were to investigate the relation between self-report measures of emotional intelligence, pre-competitive anxiety, and performance among students during the physical education exam of the high school final year. This cross-sectional study was conducted on a sample of 350 students attending the physical education exam in the year 2021-2022. Analysis of the correlations between the scores of Emotional intelligence and anxiety showed that self-confidence was positively correlated with all dimensions of Emotional intelligence (Beta=0.524; p=0.000). Multivariate linear regression analysis showed that the most related items to performance were self-confidence in a positive direction (r= 0.56; p=0.000) and negatively with somatic anxiety (r=-0, 39; p=0.000). Considering the Emotional intelligence subscales, hetero-emotional management was significantly positively associated with performance (p=0.000) however emotional perception was negatively correlated with performance (p=0.003). These results demonstrate the importance of social and emotional learning programs for improving self-confidence and better management of emotions during physical education and sports.